Binary Option sebagai Komoditi Perdagangan Berjangka di Indonesia - Danastri Puspitasari; Faiq Rizqi Aulia Rachim (Jurnal Hukum Lex Generalis, 2021)
A Binary Option is a financial product in which parties that are involved in the transaction are assigned one of two options in a certain time period. Juridically, Binary Option legality as one of commodity futures is still debatable. To be considered as commodity futures must fulfill the “futures contract” phrase in Commodity Futures Trading Act. Referring to the contract objective requirement, it’s needed to fulfill an admissible clause which Binary Option is still questionable in its contract validity.  From the consumer side, without any Bappebti license, Binary Option consumer protection is still kept in the dark either juridically or practically.